Analysis of Bacterial Diversity in Different Heavy Oil Wells of a Reservoir in South Oman with Alkaline pH. (21st March 2018) - Shibulal, Biji; Al-Bahry, Saif N.; Al-Wahaibi, Yahya M.; Elshafie, Abdulkadir E.; Al-Bemani, Ali S.; Joshi, Sanket J.
Abstract : The identification of potential hydrocarbon utilizing bacteria is an essential requirement in microbial enhanced oil recovery (MEOR). Molecular approaches like proteomic and genomic characterization of the isolates are replacing the traditional method of identification with systemic classification. Genotypic profiling of the isolates includes fingerprint or pattern-based technique and sequence-based technique. Understanding community structure and dynamics is essential for studying diversity profiles and is challenging in the case of microbial analysis. The present study aims to understand the bacterial community composition from different heavy oil contaminated soil samples collected from geographically related oil well areas in Oman and to identify spore-forming hydrocarbon utilizing cultivable bacteria. V4 region of 16S rDNA gene was the target for Ion PGM™. A total of 825081 raw sequences were obtained from Ion torrent from all the 10 soil samples. The species richness and evenness were found to be moderate in all the samples with four main phyla, Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria, the most abundant being Firmicutes. Bacillus sp. ubiquitously dominated in all samples followed by Paenibacillus, which was followed by Brevibacillus, Planococcus, and Flavobacterium . Principal Coordinate Analysis (PCoA) and UPGMA dendrogram clustered the 10 soil samples into four main groups. Weighted UniFrac significance test determined that there was significant difference in the communities present in soil samples examined. It can be concluded that the microbial community was different in all the 10 soil samples with Bacillus and Paenibacillus sp. as predominating genus. The 16S rDNA sequencing of cultivable spore-forming bacteria identified the hydrocarbon utilizing bacteria as Bacillus and Paenibacillus sp. and the nucleotide sequences were submitted to NCBI GenBank under accession numbers KP119097–KP119115. Bacillus and Paenibacillus sp., which were relatively abundant in the oil fields, can be recommended to be chosen as candidates for hydrocarbon utilization study.